COMPARISON BIOCOAGULAN EFFECTIVENESS OF MORINGA SEED (Moringa oleifera) AND SOYBEAN (Glycine max) TO REDUCE IRON (Fe) AND TURBIDITY IN BORED WELL WATER - Adnan, Fahrizal; Nugroho, Searphin; Tandi, Mardiana Lestari (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Groundwater is a source of raw water for living things. Groundwater can be obtained from drilling wells. Groundwater from drilled wells can be directly used, but some require processing before it becomes usable raw water. This research conducted water treatment by means of coagulation, flocculation, and precipitation to reduce iron and turbidity in bore well water using coagulants from extracts of moringa seeds and soybeans. Compounds in moringa seeds and soybeans that act as coagulants are proteins. This research was conducted to determine the best coagulant between moringa seeds and soybeans using a concentration of 30 mL/L, as well as determine the optimum coagulant concentration from the selected coagulant extract. The concentration variations used in the selected coagulant extracts were 10 mL, 20 mL/L, 30 mL/L, 40 mL/L, and 50 mL/L. The results showed that the optimal coagulant extract was moringa seeds with a decrease in turbidity to 109.79 NTU (4.5%) from 115 NTU and iron to 0.36 mg/L (92.73%) from 4.95 mg/L. The optimal concentration of coagulant concentration variations of Moringa seed extract is 10 mL/L with a decrease in turbidity to 69.76 NTU (39.34%) from 115 NTU and iron to 0.034 mg/L (99.31%) from 4.95 mg/L. Keywords: Coagulation, Moringa Seeds, Soybeans, Iron, Turbidty